Global research trends in biomaterials over the past 20 years: a bibliometric and visualization study - Fanyu Meng (446249) (2025)
As an interdisciplinary discipline bridging medicine and engineering, Biomaterials have garnered increasing research attention in recent years, with evolving research hotspots. This study analyzed 122,146 publications in Biomaterials from the Web of Science Core Collection database using VOSviewer software for bibliometric analysis over the past 20 years. Results revealed sustained rapid growth in publications, with China and the United States of America as leading contributors, and the Chinese Academy of Sciences consistently ranking as the top institution. Keyword analysis demonstrated a thematic evolution: the first phase focused on technological exploration topic like ‘tissue engineering’, ‘hydrogels’, ‘nanoparticles’, while the second phase emphasized application-oriented topics like ‘antibacterial’ and ‘wound healing’, highlighting the discipline’s shift from fundamental research to practical medical applications. The findings can delineate developmental trajectories and emerging frontiers in Biomaterials, offering empirical insights for researchers to identify trends and guide future directions in the discipline.